2014
DOI: 10.5935/abc.20140210
|View full text |Cite
|
Sign up to set email alerts
|

Microparticles as Potential Biomarkers of Cardiovascular Disease

Abstract: Primary prevention of cardiovascular disease is a choice of great relevance because of its impact on health. Some biomarkers, such as microparticles derived from different cell populations, have been considered useful in the assessment of cardiovascular disease. Microparticles are released by the membrane structures of different cell types upon activation or apoptosis, and are present in the plasma of healthy individuals (in levels considered physiological) and in patients with different pathologies. Many stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 61 publications
0
28
0
2
Order By: Relevance
“…However, in response to activation processes and/or apoptosis, the number of EMVs increases significantly. Physiological blood levels of EMVs present in healthy individuals are between 10 3 and 10 4 EMVs/mL and pathological concentrations (present in individuals with CVD) are 10 5 EMVs/mL [99]. Several authors have found that mature endothelial cells in culture, exposed to activation by cytokines, released more EMVs [100,101].…”
Section: Microvesicles and Endotheliummentioning
confidence: 99%
“…However, in response to activation processes and/or apoptosis, the number of EMVs increases significantly. Physiological blood levels of EMVs present in healthy individuals are between 10 3 and 10 4 EMVs/mL and pathological concentrations (present in individuals with CVD) are 10 5 EMVs/mL [99]. Several authors have found that mature endothelial cells in culture, exposed to activation by cytokines, released more EMVs [100,101].…”
Section: Microvesicles and Endotheliummentioning
confidence: 99%
“…Nuestros resultados mostraron que la liberación de MV se incrementó en las células endoteliales tratadas con IS y podría asociarse con el porcentaje de células endoteliales senescentes. En referencia a la liberación de MV de las células endoteliales, algunos estudios mostraron que las células endoteliales dañadas liberan un mayor número de MV [8,9], lo que confirma nuestros datos obtenidos mediante el tratamiento con IS. Estos datos representan una ventaja en la identificación de pacientes con ERC con una lesión endotelial.…”
Section: Discussionunclassified
“…Las MV influyen sobre la regulación de la homeostasis al participar en la comunicación intercelular. Sin embargo, en condiciones patológicas, las células dañadas son capaces de liberar distintas cantidades de MV que se caracterizan por transportar moléculas diferentes, promoviendo una serie de cambios que pueden desencadenar daños en otras células de tejidos adyacentes [8][9][10]. En concreto, aquellas producidas por células endoteliales se pueden cuantificar en sangre periférica y usarse como posible biomarcador para evaluar el daño endotelial [3,11,12].…”
Section: Introductionunclassified
“…Raise of microparticle concentrations is also associated with hypertension (Preston et al 2003), atrial fibrillation (Ederhy et al 2007) or pulmonary hypertension (Diehl et al 2011). Increased levels microparticles were further found in metabolic diseases such as obesity, diabetes (Sabatier et al 2002, Tramontano et al 2010, França et al 2015, and dyslipidemia (Boulanger et al 2006). Furthermore, elevated microparticles could be strong predictor for complications in pregnancy, namely in the case of life threatening preeclampsia (Van Wijk et al 2002, Bretelle et al 2003, Gonzales-Quinteiro et al 2004, but also in septic shock in general population of patients (Zafrani et al 2013, Zhang et al 2016).…”
Section: Introductionmentioning
confidence: 99%